The Neurotensin-Induced Release Pathway of Vascular Endothelial Growth Factor in Human Mast Cells. - Kearns, Malcolm D. (Tufts Archival Research Center, 2005)
Mast cells are immunocompetent cells located throughout the body, their function dictated by the specific microenvironments of the tissues in which they reside. Storing or synthesizing de novo a variety of chemicals, mast cells release mediators by selective secretion or compound exocitosis that are involved in host defense, allergy, inflammation, and in the growth of some tumors. One such mediator, Vascular Endothelial Growth Factor (VEGF), is crucial to both physiological angiogenesis and the angiogenesis associated with pathological conditions such as tumor growth. Our lab has previously shown that the neuroendocrine peptide neurotensin (NT) causes an increase in the expression of VEGF isoforms in HMC-1 cells mast cells and mediates VEGF release through an NT-specific NTS-1 receptor. This project sought to confirm and extend these findings by exploring additional 'downstream' components of the VEGF release pathway, identifying several enzyme mediators that, when selectively inhibited, block the release of VEGF following NT stimulation. Selectively inhibiting MEK1 MAPK, PKC, PKA, p38 MAPK, and PI3-Kinase have shown significant decreases in VEGF release following NT-stimulation of HMC-1 cells. In addition, a Zinc chelator blocked the release of VEGF. Western blotting was used to confirm these observations. This research may be applied to the understanding of human cancers, as mast cells have been shown to accumulate around various tumors. In addition, various cancer cells have been shown to secrete NT. Thus, the release of a pro-angiogenic factor from mast cells by NT stimulation may be tied to the blood supply required by growing tumors. Knowledge of these cellular interactions may provide valuable insight into tumor growth and development.